Bankruptcy Prediction Analysis Using the Springate and Zmijewski Methods at PT Krakatau Steel (Persero) Tbk. - Ilmani Ganis Adzillah; Djoni Djatnika; Rosma Pakpahan; Ulfah Nurul Fauziah (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
PT. Krakatau Steel (Persero) Tbk is the first steel-producing industry in Indonesia and was founded in 1970. In researching the company, two methods were used to predict the potential for bankruptcy: the Springate and Zmijewski methods. This type of research is descriptive research. The data used in this study is secondary data from PT Krakatau Steel (Persero) Tbk for the period 2016-2021. The results of this study indicate that based on the Springate method, PT. Krakatau Steel is predicted to go bankrupt. While the results obtained from the Zmijewski method show that from 2016 to 2018, PT. Krakatau Steel is predicted not to go bankrupt. However, in the calculations from 2019 to 2021, the Z value obtained is far above the value 0, which is the applicable cut-off value. This shows that PT. Krakatau Steel is predicted to go bankrupt.